1988
DOI: 10.1007/bf00570128
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of aromatic amines II: hemoglobin binding of some monocyclic aromatic amines

Abstract: Covalent binding of 13 monocyclic aromatic amines to hemoglobin was studied in female Wistar rats and hemoglobin binding indices were determined. The hemoglobin adducts were hydrolyzed under alkaline conditions. In all cases the parent amine could be identified by gas chromatography and with one exception represented the only cleavage product. The binding index varied considerably and was highest with p-chloroaniline (569) and lowest with 2,4,5-trimethylaniline (0.7). Five compounds were also studied in female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 14 publications
1
37
0
1
Order By: Relevance
“…Accordingly, although in our study, gavage, rather than inhalation, was the favored route of administration, the MetHb concentrations in blood were indistinguishable from those in the control group (data not shown), because the samples were collected the next day after finishing NMA administration. Besides, assessment of blood MetHb concentration is made difficult by the high activity of N-acetylotransferase -the enzyme involved in MetHb metabolism [21]. Clinical analysis of the key parameters confirmed that NMA, as aniline derivative, is hepatotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, although in our study, gavage, rather than inhalation, was the favored route of administration, the MetHb concentrations in blood were indistinguishable from those in the control group (data not shown), because the samples were collected the next day after finishing NMA administration. Besides, assessment of blood MetHb concentration is made difficult by the high activity of N-acetylotransferase -the enzyme involved in MetHb metabolism [21]. Clinical analysis of the key parameters confirmed that NMA, as aniline derivative, is hepatotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…Amines with one amine group such as aniline and 4ABP are more useful when acetylation can be explained in the evaluation of exposure to hemoglobin adducts 17) since the risk for bladder cancer increases when Nhydroxylation increases competitively due to slowly progressing N-acetylation 61,62) . However, it is difficult to explain for toxicity and solubility only with N-acetylation because deacetylation and N-acetylation occur at the same time in amines with more than 2 amine groups such as BZ 29) .…”
Section: Discussionmentioning
confidence: 99%
“…In such a situation the first step must accomplish release of the primary analytes. Conjugates can be cleaved by acid hydrolysis [168][169][170][171], basic hydrolysis [170], or enzymatic hydrolysis [170], [172]. Hydrolysis with the aid of enzymes, such as sulfatase and glucuronidase, has the significant advantage that bonds are cleaved extremely selectively, and information can also be obtained regarding the binding partners of the analyte.…”
Section: Hydrolysismentioning
confidence: 99%
“…For example, analytes containing carboxyl groups are often converted into methyl [164], [169], pentafluorobenzyl [274][275][276][277], or triethyl esters [278][279][280]. Analytes containing acidic hydroxyl groups (phenols, chlorophenols, glycol ethers) or amino groups (e.g., aniline) can be derivatized with such perfluorinated compounds as heptafluorobutyric anhydride, pentafluoropropionic anhydride [177], or pentafluorobenzoyl chloride [281].…”
Section: Derivatizationmentioning
confidence: 99%